Anti-Hero Design to Grow the Meaning of Heroes from the Comic Entitled "Second Shot" - Louis Arthur Robianto; Heru Dwi Waluyanto; Asthararianty Asthararianty (k@ta: A Biannual Publication on the Study of Languange and Literature, 2024)
Development of digital era encourages creative industry to continue grow by raising many issues, nowadays many are found in various visual media using anti-hero characters as main character. Anti-hero is hero character who has traits and characters that deviate from depiction of a hero in general (Bagaskara, 2021). They have the same goal of doing good but in a way that may sometimes be wrong or unjustified (Wahyudi, 2020). This character is very appropriate to express human imperfection which in life always has advantages and disadvantages. In contrast to superhero characters who are too perfect to be used as exemplary figures in real life. The media that will be used is comic with theme entitled "The Second Shot" where main character who is half human and alien will be faced with many choices that can determine the future of the world, besides being disappointed or having hidden hatred as well. From past events from both human side who had deceived him and aliens who only took advantage of him. The use of comics media as visual media is based on fact that target audience is younger generation between ages 18-25 years who are more interested in reading picture books than those that contain too many words.